The properties of the equilibrium solutions of one class of the complex problems - Jasilionis, R. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Ю. Ясилионис. О свойствах равновесных решений одного класса сложных задач R. Jasilionis. Apie vienos sudėtingų uždavinių klasės pusiausvyros sprendinių savybes